An exploration of female offenders' yoga experience in Worcester's correctional centre - Van Rooyen, Karla (Department of Public Law, 2025)
In South Africa, there has been a lack of research on female offenders' incarceration experience. Research shows that female offenders are a vulnerable group with specific needs that deserve specialised treatment options. Yoga has become very popular as a holistic rehabilitation programme within many correctional centres, including South Africa. Yoga has become a symbolic resource that offenders can use to make sense of their incarceration experience and re(construct) their self-perception, while still incorporating ‘peace-making-mechanisms' that fit into correctional centres' agenda. This study explores the impact of a yoga programme called ‘The Freedom Project' in Worcester Correctional Centre. The objective of this study was to determine whether or not yoga could transform female offenders' behavioural patterns and help them cope with the pains of imprisonment. A qualitative research design allowed for rich accounts of the participants' yoga experience. The interviews were conducted with a panel of nine female offenders who participated in the yoga programme. While the design of the study makes it difficult to generalize the findings to the wider offending population, the participants nonetheless offered evidence that yoga is a life-affirming experience with a range of transformational consequences. The results of the study showed that the yoga programme allows for an open framework, and freedom of self-exploration and meets the goals of being a more women-centred and holistic approach within prison reform.